Le rôle de l’intertexte et du palimpseste dans la création d’une Écosse mythique dans Waverley et Rob Roy de Walter Scott - Céline SABIRON (E-REA)
Recently united to its powerful English twin sister through the 1707 Union Act, Scotland experiences a major identity crisis in the Enlightenment. Politically, religiously, and socially divided, it is led to redefine its image by rewriting history through mythology. A myth is “a speech, a system of communication, a message”, Roland Barthes explains in Mythologies. This message of an identity re-creation is relayed by Walter Scott’s Scottish novels, in particular Waverley and Rob Roy which describe Scotland and its inhabitants through the gaze of naive English scholars. Far from being realistic, this textual portrait is made of a superimposition of mythical and literary images, especially when describing the Highlands. Besides, the characters, such as the popular historical outlaw Rob Roy, are romanticized and mythicized in these fictions which recount the 1715 and 1745 Jacobite Risings in an epic style. Scott’s pictorial language also participates in conveying a mythical image of Scotland.We will thus try and explain the motives of such a meshing of fictive images taken from mythical and literary works, and see how these various pictures are woven together by means of rhetorical images to shape a new Scottish identity.